Introduction of the speaking rate in the model of speech recognition - Abdellah Yousfi; Abdelouafi Meziane (International Journal of Mathematics and Mathematical Sciences)
We propose an improvement to the centisecond TLHMM model (Meziane, 1999) applied to the sound duration. Indeed, the distribution of the sound duration depends on the speaking rate. An adaptation in a post-processing step is needed. This adaptation is studied by proposing a model of the speaking rate based on average syllabic duration. The experiments elaborated on a set of BDSONS show the interest of this approach. This work is a continuation of those by Meziane (1999) and Suaudeau (1994).